Discounted labour : women workers in Canada, 1870-1939 - Frager, Ruth A., 1950-; Patrias, Carmela, 1950- (Themes in Canadian social history., 2005)
Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada.